Ответы и объяснения

2013-09-04T12:31:59+04:00
2y-7-y+10                      y+3                   1
-----------------------      =   --------------  =    -------------
y^{2} -9           (y+3)(y-3)         y-3

при  y=2,1     
  1                1               10              1
--------  =  ---------- =  - -------------  =  -1 ----
2,1-3        -0,9               9                 9         .

при y=-2
    1            1                1
---------  =  ----------  =  -  ---------
y-3            -2-3              5